ANALISIS KANDUNGAN BESI (Fe), MANGAN (Mn), DAN pH AIR TANAH HASIL PEMBORAN GEOTEKNIK DI TAMBANG BATUBARA PT ADARO INDONESIA KABUPATEN TABALONG DAN BALANGAN PROVINSI KALIMANTAN SELATAN - Suhernomo Suhernomo; Athailllah Mursyid; Emmy Sri Mahreda; Gusti Chairuddin (EnviroScienteae, 2014)
One of PT. Adaro Indonesia environment management responsibilities is the water management aspect. The management of ground water, that potentially becomes fresh water still combined with the run off water management. It means that ground water is still treated as waste water that needs to be re-managed. This research is intended to know the feasibility ground water quality of Fe, Mn, and pH parameter as fresh water refers to Peraturan Menteri Kesehatan No. 416 tahun 1990 Tentang Syarat-Syarat dan Pengawasan Kualitas Air  (an Indonesia Ministry of Health rules related to water quality requirements and water quality monitoring).The result of this ground water research shows that the water pH in all fifteen research locations has not met the fresh water quality standard as standartstated (water pH below 6.5 – 9). Only five research locations that Fe parameter meetthe quality standart, four ground water locations and one from WTP T300 location. High Fe concentration is caused by Fe2+ or Fe3+ ions that does not get oxygen from the atmosphere and it is also caused by lithology or rock formation that is dominated by iron mineral which lead to need of further management such as aeration.  Manganese parameter in all research locations is still met the quality standards as stated in Peraturan Menteri Kesehatan No. 416 tahun 1990 Tentang Syarat-Syarat dan Pengawasan Kualitas Air, which means it is still under 0.5 mg/L quality standards. It can be generally concluded that the Fe parameter in research locations is still has not met fresh water quality standards in such a way that can influence the pH values. For the Mn parameter, all research locations are still met the fresh water quality standards.